Academic Scholarship in Light of the 2008 Financial Crisis: Textual Analysis of NBER Working Papers - Daniel Levy; Tamir Mayer; Alon Raviv (Bar-Ilan University, Department of Economics, 2020)
Textual analysis of 14,270 NBER Working Papers published during 1999–2016 is done to assess the effects of the 2008 crisis on the economics literature. The volume of crisis-related WPs is counter-cyclical, lagging the financial-instability-index. WPs by the Monetary-Economics, Asset-Pricing, and Corporate-Finance program members, hardly refer to “crisis/crises” in the pre-crisis period. As the crisis develops, however, their study-efforts of crisis-related issues increase rapidly. In contrast, WPs in macroeconomics-related programs refer quite extensively in the pre-crisis period to “crisis/crises” and to crises-related topics. Overall, our findings are consistent with the claim that economists were not engaged sufficiently in crises studies before the 2008 crisis. However, counter to the popular image, as soon as the crisis began to unravel, the NBER affiliated economists responded dramatically by switching their focus and efforts to studying and understanding the crisis, its causes and its consequences.
Keywords: A11; C38; C55; E32; E44; E58; F30; G01; G20; G21; G28; 330; 2008 Financial Crisis; Textual Analysis; Financial Crises; LDA; Topic Modelling; Securitization; Repo; Sudden Stop